Analisis Faktor-Faktor yang Mempengaruhi Minat Perilaku Penggunaan Sistem Informasi Akuntansi Berbasis E-Commerce - Putri Shanny Freolina; Lukita Tripermata; Rafika Sari (Syntax Idea)
The purpose of this study was to determine the effect of attitudes, subjective norms, perceived usefulness, perceived ease of use on behavioral interest in using e- commerce-based accounting information systems in online sales applications among college students. The population of this study were students of the 2019- 2020 accounting study program, Indo Global Mandiri University, Palembang. The sample used in this study were 107 respondents. The research data is primary data obtained through distributing questionnaires. In this study the sampling technique was taken using nonprobability sampling techniques, data processing methods using multiple linear analysis with data analysis tools using SPSS 26. The results of this study indicate that attitudes, subjective norms, perceived ease of use, have a positive and significant effect on interest in using information systems e-commercebased accounting on online sales applications, while Perceived Usefulness has no positive and not significant effect on behavioral intention to use e-commerce based accounting information systems.